2013
DOI: 10.1080/10538712.2013.735355
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Young Adult Male Sex Offenders: Understanding the Role of Recidivism

Abstract: The current review explores the complex paths that can lead to adolescent and young adult males becoming sexually abusive. Because sexual abuse is an ongoing issue in our society that is often oversimplified, this article distinguishes between the various risk factors that predict sexually abusive behavior and types of sex offenders, particularly recidivistic offenders. It is imperative to focus on adolescents and young adults who sexually abuse because they represent a particularly important intervention poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 71 publications
1
21
0
1
Order By: Relevance
“…Riser et al . 's () narrative review defines recidivism as reoffending. Recidivism is measured using either reconviction rates or self‐reporting by offenders.…”
Section: Resultsmentioning
confidence: 99%
“…Riser et al . 's () narrative review defines recidivism as reoffending. Recidivism is measured using either reconviction rates or self‐reporting by offenders.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure total anonymity we agreed that the LSCB would remain anonymous in any subsequent publication. Consequently, the data we used came from a social history protocol we designed based upon international research that identified a range of factors that was associated with Youths (518) who later became adult (18þ) Child-Sex-Abusers, to determine whether these Youths had similar characteristics (Almond, Canter, & Salfati, 2006;Craig et al, 2008;Christiansen & Vincent, 2013;Finkelhor, 2009;Pritchard, 2004;Reavis et al, 2013;Riser et al, 2013;Roe-Sepowitz & Krysik, 2008;Witztum et al, 2012;Wortley & Smallbone, 2014). We could not find a standardised questionnaire or protocol that was indicative of youths who posed a potential sexual risk to children.…”
Section: Methodsmentioning
confidence: 99%
“…Youths were either former or current LAC, or former Excluded-from-School (EFS) with those who were not 3. Youths who had been Formally Charged with a sex offence against another child versus those who had not been charged This last comparison is undertaken because a formal charge of a sex offence against a child within the general population is statistically extremely rare (Pritchard & Williams, 2009) and consequently might be considered as a serious indication that the young person is already at risk of recidivism (Christiansen and Vincent, 2013;Finkelhor, 2009;Reavis et al, 2013;Riser et al, 2013;Whitaker et al, 2012;Wortley & Smallbone, 2014).The subgroups were statistically tested using the non-parametric chi square test, which is appropriate for relatively small numbers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research concerning sexual arousal of adolescent sex offenders, which indicates that their sexual interests and arousal are less fixated and more fluid, would appear to support this conclusion. The path to becoming sexually abusive appears to be complex (Riser et al 2013).…”
Section: Characteristics Of Juvenile Sex Offendersmentioning
confidence: 99%